3-T Breast Diffusion-Weighted MRI by Echo-Planar Imaging With Spectral Spatial Excitation or With Additional Spectral Inversion Recovery. Issue 3 (May 2015) - Jacobsen, Megan C.; Dogan, Basak E.; Adrada, Beatriz E.; Plaxco, Jeri Sue; Wei, Wei; Son, Jong Bum; Hazle, John D.; Ma, Jingfei
<x xml:space="preserve">Abstract</x> Objective To compare conventional diffusion-weighted imaging (DWI) with spectral spatial excitation (cDWI) and an enhanced DWI with additional adiabatic spectral inversion recovery (eDWI) for 3-T breast magnetic resonance imaging (MRI). Methods Twenty-four patients were enrolled in the study with both cDWI and eDWI. Three breast radiologists scored cDWI and eDWI images of each patient for fat-suppression quality, geometric distortion, visibility of normal structure and biopsy-proven lesions, and overall image quality. Signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and apparent diffusion coefficient (ADC) for evaluable tissues were measured. Statistical tests were performed for qualitative and quantitative comparisons. Results Diffusion-weighted imaging with spectral spatial excitation yielded significantly higher CNR and SNR on a lesion basis, and higher glandular CNR and SNR and muscle SNR on a patient basis. Enhanced DWI also yielded significantly higher qualitative scores in all categories. No significant difference was found in ADC values. Conclusions Enhanced DWI provided superior image quality and higher CNR and SNR on a lesion basis. Enhanced DWI can replace cDWI for 3-T breast DWI.